Kajian Penyediaan Varietas Jagung untuk Lahan Suboptimal - Sutoro, Sutoro (Iptek Tanaman Pangan, 2012)
Hybrid and composite maize varieties are cultivated under different soil types in uplands and lowlands, as well as under suboptimum condition. Drought stress, acidic soil, and low fertility could be overcome by using adaptive cultural techniques coupled with planting of maize varieties which adaptive to abiotic stress. The number of maize varieties adaptive to abiotic stress was still limited, therefore development of corn hybrid and composite varieties should be done under specific environment. Maize hybrids produce more yield than do composite varieties, but composite varieties are more adaptive to less productive environments. Composite (synthetic or open pollinated) varieties are needed to increase maize production under suboptimum condition and to increase farmer’s income. Seeds of maize varieties adaptive to suboptimum condition need to be produced and distributed to farmers by involving seed growers and farmers groups.